Effect of Ti on the microstructure change and oxidation behavior of Ni+CrAlYHfSiN composite coatings. (15th April 2019) - Ren, Pan; Yang, Yingfei; Zhu, Shenglong; Wang, Fuhui
Highlights: The effect of Ti on oxidation resistance and microstructural evolution of two composite coatings were studied. Ti from substrate reacted with [N] ions in composite coatings and formed TiN in reaction zone. The position of reaction zone was determined by the relative content of [N] ions and metallic Al in composite coatings. The transportation of   T i A l ∙ in alumina resulted in a higher oxidation rate of coating. Abstract: Two composite coatings are manufactured by reactive magnetron sputtering on superalloys. The effect of titanium on oxidation resistance and microstructural change of composite coatings were studied. Titanium in superalloys reacted with [N] ions in composite coating due to interdiffusion. The position of reaction zone was determined by the relative content of [N] ions and metallic aluminum in coating. Doping of titanium in alumina lead to a decrease of charged oxygen vacancies but Ti Al forms in this process. The transportation of Ti Al in oxide scale resulted in the formation of TiO2 and a higher oxidation rate of coating.